What Helped Nonprofits Weather the Great Recession?: Evidence from Human Services and Community Improvement Organizations. Issue 3 (22nd December 2015) - Lin, Weiwei; Wang, Qiushi
Abstract: This study examined the effectiveness of several financial strategies for nonprofit organizations in fighting the Great Recession. Using data from human services and community improvement organizations in the state of New Jersey, we tested hypotheses about the relationships between three measures of financial sustainability and various fundraising efforts and financial indicators. We found that (1) except for strong external funding relationships, funding efforts were generally not effective in enhancing financial sustainability during the crisis; (2) higher operating margin and equity ratio improved an organization's ability to generate revenue and maintain expense levels, but higher debt ratio and administrative cost ratio were generally harmful; and (3) revenue diversification might aggravate fiscal stress and cause more expense cuts in a severe crisis. These findings improve our understanding of the mechanics of nonprofit management during times of harsh fiscal conditions and suggest useful ways for nonprofit organizations to navigate future financial crises.